Mapping the landscape of PSC-CM research through bibliometric analysis - Li, Jun; Han, Shangting; Yu, Fengxu; Li, Tao; Liao, Bin; Liu, Feng (Frontiers in Cardiovascular Medicine, 2024)
The discovery of pluripotent stem cell-derived cardiomyocytes (PSC-CMs) has not only deepened our understanding of the pathogenesis and progression of heart disease, but also advanced the development of engineered cardiac tissues, cardiac regenerative therapy, drug discovery and the cardiotoxicity assessment of drugs. This study aims to visualize the developmental trajectory of PSC-CM research over the past 18 years to identify the emerging research frontiers and challenges.The literature on PSC-CMs from 2007 to 2024 was retrieved from the Web of Science database.Bibliometrix, VOSviewer and CiteSpace software were used for statistical analysis and visualization of scientific literature. Previous clinical trials were summarized.A total of 29,660 authors from 81 countries and regions published 6,406 papers on PSC-CMs over the past 18 years. The annual output of PSC-CM research experienced a general upward trend from 2007 to 2021, reaching its peak in 2021, followed by a notable decline in 2022 and 2023. The United States has emerged as the most influential nation in this field, with Stanford University being the most prolific institution and Joseph C. Wu standing out as the most productive and highly cited scholar. Circulation Research, Circulation, and Nature have been identified as the most co-cited journals.Organ-on-a-chip, 3D bio-printing, cardiac microtissue, extracellular vesicle, inflammation, energy metabolism, atrial fibrillation, personalized medicine etc., with a longer burst period, and maturation of PSC-CMs, with the highest burst strength of 27.19, are the major research focuses for rigorous investigation in recent years. Cardiac organoid is emerging as a promising key research frontier. While the clinical trials of stem-cell-mediated treatment for heart diseases shows promise, significant challenges remain. Further research is imperative to optimize protocols, enhance cell delivery methods, and establish standardized practices to improve clinical outcomes.In conclusion, several major research hotspots, including engineered cardiac tissue and maturation, exosome-based regenerative therapy, inflammation response, energy metabolism, atrial fibrillation, and personalized medicine etc. will continue to attract substantial interest from investigators worldwide. Cardiac organoids to in vitro recapitulate the intricate human heart is emerging as a promising key 3 research frontier. Significant challenges persist in the clinical trials of stem-cell-mediated therapies for heart diseases.